A building modelling system for environmental design - Pavey, S. G. (Cranfield University, 1991)
Computerised systems have been developed to simulate the dynamic thermal performance of a building over a period of time, against a given weather pattern, with the aim of predicting the environmental and energy performance of the building. The usage of these systems has been limited, however due to the difficulty in describing the problem to be simulated to the system, and in interacting with the system. In particular the geometrical form of a building can be very tedious to input. This thesis considers the graphical creation of a building model for environmental analysis, such that the necessary geometrical data can be automatically derived and input into the analysis. Current geometrical modelling techniques and the use of CAD in building design are considered. The geometrical and topological modelling requirements for the building model are established, and a data structure is derived and checked for sufficiency. A possible modelling method is described for simple 21/2 dimensional buildings, and uses the property that the floor plan of a building can be represented by a planar graph. The necessary extensions to the modelling method are considered to allow more complex 3 dimensional forms to be created. The assignment of attributes to the model, necessary for the thermal analysis, is also included. Details arc given of the functionality of a user interface, using an implementation of this modelling method. This includes a description of the interaction to create the model, and the graphical displays that are generated. This modelling method has also been used in the development of an interface to an architectural CAD system, such that the necessary building data can be transferred for analysis.